112k views
1 vote
Jada is solving the equation shown below. -1/2 (x+4) = 6 Which is a possible first step to begin to simplify the equation? Check all that apply. Divide both sides of the equation by –2. Subtract 4 from both sides of the equation. Multiply both sides of the equation by –2. Distribute –2 over (x+4). Distribute -1/2 over (x=4). Multiply both sides of the equation by -1/2.

User ERadical
by
5.5k points

2 Answers

5 votes

Answer:

⇒ Multiply both sides of the equation by -2

⇒ Distribute -1/2 over (x+4)

Those are the 2 answers.

User XAMeLi
by
4.6k points
0 votes

Answer:

Multiply both sides of the equation by -2

Distribute -1/2 over (x+4)

Explanation:

we have


-(1)/(2)(x+4)=6

Method 1

Multiply both sides of the equation by -2 ------> Step 1


(x+4)=6*(-2)


(x+4)=-12

Subtract 4 from both sides of the equation


x=-12-4=-16

Method 2

Distribute -1/2 over (x+4)-------> Step 1


-(1)/(2)x-2=6

Multiply both sides of the equation by -2


x+4=6(-2)


x+4=-12

Subtract 4 from both sides of the equation


x=-12-4=-16

User Sheryll
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.